Pharmaceutical Entrepreneurs - Wahyu Toha Abdul Hak; Rifqoh Fauziyah (Solo International Collaboration and Publication of Social Sciences and Humanities, 2026)
Objective: This study aims to understand the definition of entrepreneurship, the characteristics of good entrepreneurs, and the types of entrepreneurs in the pharmaceutical sector. Theoretical framework: The theoretical framework of this research is based on the concept of entrepreneurship as the ability of individuals to recognize, manage, and develop their potential optimally to create added value and improve their standard of living. In the pharmaceutical sector, entrepreneurship is associated with innovation and managerial ability. Literature review: A literature review discusses the definition of entrepreneurship from various perspectives and characteristics of entrepreneurs, such as creativity, innovation, leadership, and decision-making ability. In addition, entrepreneurial opportunities in the pharmaceutical sector were also discussed. Method: Research using the systematic review method with the PRISMA approach. Articles are searched using the keyword "pharmaceutical entrepreneur" through Google Chrome, then selected based on topic relevance. Results: The results of the study show that there are two articles that are suitable for analysis. Both articles explain that entrepreneurship is the ability to manage and develop one's potential optimally to improve the quality of life. Implications: This research provides an understanding of the importance of entrepreneurship in the pharmaceutical sector and can be a reference for students and pharmacy practitioners in developing businesses in the health sector. Novelty: The novelty of this research lies in the focus of a systematic review study on entrepreneurship in the pharmaceutical sector, which is still limited, and the incorporation of the concept of entrepreneurship into the pharmaceutical sector.